
In classical logic A -> B is the equivalent to ~A v B
(with ~ = not and v = or)
So
(forall a. P(a)) -> Q
{implication = not-or}
~(forall a. P(a)) v Q
{forall a. X is equivalent to there does not exist a such that X doesn't
hold}
~(~exists a. ~P(a)) v Q
{double negation elimination}
(exists a. ~P(a)) v Q
{a is not free in Q}
exists a. (~P(a) v Q)
{implication = not-or}
exists a. (P(a) -> Q)
These steps are all equivalencies, valid in both directions.
On Wed, Aug 15, 2012 at 9:32 AM, David Feuer
On Aug 15, 2012 3:21 AM, "wren ng thornton"
wrote: It's even easier than that.
(forall a. P(a)) -> Q <=> exists a. (P(a) -> Q)
Where P and Q are metatheoretic/schematic variables. This is just the usual thing about antecedents being in a "negative" position, and thus flipping as you move into/out of that position.
Most of this conversation is going over my head. I can certainly see how exists a. (P(a)->Q) implies that (forall a. P(a))->Q. The opposite certainly doesn't hold in classical logic. What sort of logic are you folks working in?
_______________________________________________ Haskell-Cafe mailing list Haskell-Cafe@haskell.org http://www.haskell.org/mailman/listinfo/haskell-cafe